2022
DOI: 10.1155/2022/5315927
|View full text |Cite|
|
Sign up to set email alerts
|

Network-Based Elaboration of the Efficacy of the Dachangshu (BL25) and Tianshu (ST25) Points in the Treatment of Functional Constipation in Children through Inflammation, Adipocytokine, or Leptin Pathways

Abstract: Constipation commonly occurs during childhood, and more than 95% of cases are classified as functional constipation. If not effectively treated, 20% of patients with childhood constipation can continue to exhibit symptoms into adulthood, which seriously affects their mental health and quality of life. The main feature of acupuncture or acupoint stimulation, a special branch of traditional Chinese medicine, is the selection of different acupoints for different diseases, and many worthy guidelines have been esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The Neiguan (PC 6) acupoint is the collateral point of the pericardial meridian of the Hand-Jueyin. Acupuncture at this point is also very important, as it can effectively strengthen endocrine function, especially after the combined use of adrenaline and vasopressin, and reduce the secretion of gastric acid over time[ 16 , 17 ]. However, in the present study, this acupoint was not selected because the distance between the acupoint and the wound was too short to avoid infection to the wound.…”
Section: Discussionmentioning
confidence: 99%
“…The Neiguan (PC 6) acupoint is the collateral point of the pericardial meridian of the Hand-Jueyin. Acupuncture at this point is also very important, as it can effectively strengthen endocrine function, especially after the combined use of adrenaline and vasopressin, and reduce the secretion of gastric acid over time[ 16 , 17 ]. However, in the present study, this acupoint was not selected because the distance between the acupoint and the wound was too short to avoid infection to the wound.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%